2018
DOI: 10.1177/1044207318793158
|View full text |Cite
|
Sign up to set email alerts
|

Policy and Program Considerations for Choosing Crisis Intervention Programs

Abstract: Recently there has been national media attention focusing on the number of deaths and injuries associated with the use of physical restraint and seclusion procedures in schools. Research shows these procedures are most frequently applied to students with disabilities, and that lack of staff training in de-escalation procedures, as well as the use of these interventions, is commonly viewed as a contributing factor to student injuries and death. This study compares and contrasts crisis intervention training from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The importance of mandated reporting to parents within 24 hours-including providing written documentation, engaging in follow-up debriefing with parents and school personnel, and collecting, analyzing, and disseminating data are considered best practices and have been mandated in many U.S. states (Butler, 2019;Couvillon et al, 2019;US Department of Education, 2012). While some provinces have mandated documentation and reporting practices that include a requirement for same day written notification and for follow-up debriefing and planning with both parents and school it is not a universal requirement.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The importance of mandated reporting to parents within 24 hours-including providing written documentation, engaging in follow-up debriefing with parents and school personnel, and collecting, analyzing, and disseminating data are considered best practices and have been mandated in many U.S. states (Butler, 2019;Couvillon et al, 2019;US Department of Education, 2012). While some provinces have mandated documentation and reporting practices that include a requirement for same day written notification and for follow-up debriefing and planning with both parents and school it is not a universal requirement.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Research indicates that preventive approaches can effectively reduce dangerous behaviors (Bullock & Gable, 2000; Miller et al, 2005). Unfortunately, educators who are not trained in prevention and de-escalation techniques risk exacerbating student behavior (Colvin, 2004; Couvillon et al, 2019). In addition, research has shown that the threat or use of seclusion often escalates student behavior.…”
Section: Common Challenges With Timeoutmentioning
confidence: 99%
“…Although many special education programs in schools engage private vendors for “crisis intervention training,” such training only rarely addresses seclusion. Couvillon and colleagues (2018) reported that only four of 17 commercial crisis/de-escalation programs included training on seclusion (Couvillon, et al, 2018). Such training was often only provided when requested or required by a state.…”
Section: Problems With the Use Of Seclusionmentioning
confidence: 99%
“…Because of the critical importance of de-escalation to avoid the use of seclusion, it is necessary to highlight considerations for training educational personnel in this skill area. Schools often rely on outside vendors for staff training and Couvillon et al (2018) found that time spent on de-escalation strategies varied considerably by vendor. They recommended that school programs examine internal and state polices as well as vendor training time spent on de-escalation prior to choosing a vendor for training.…”
Section: Strategies To Eliminate the Use Of Seclusionmentioning
confidence: 99%